PENGARUH FLY ASH SEBAGAI PENGGANTI SEBAGIAN SEMEN TERHADAP KUAT TEKAN BETON SELF COMPACTING CONCRETE (SCC) - Prasetiyo, Firmansyah Risqi; Nuradiana, Anita Intan; Sutowijoyo, Hendro (Program Studi Teknik Sipil Universitas Narotama, 2024)
ABSTRACT Self Compacting Concrete (SCC) is concrete that is able to compact itself without using a compactor or vibrator. Therefore, to reduce the use of cement in the Self Compacting Concrete (SCC) concrete mixture, admixture is used as a partial replacement for cement. The additional material used in this research is fly ash. Fly ash is the residue from burning coal which contains pozzolanic elements (SiO2, Al2O3 and Fe2O3) so that it can fill voids and become a binding material like cement. This research is experimental carried out in the laboratory. This research design carries out. This mixing carried out 3 variations of fly ash, 10%, 20% and 50%, while the addition of superplasticizer was 1%. This research was to determine of adding fly ash and superplasticizer on compressive strength. The compressive strength test for Self Compacting Concrete (SCC) concrete was carried out at ages 3, 14, 28 days. Based on the test results, it is known that the workability and compressive strength of Self Compacting Concrete (SCC) decreases as the fly ash content increases. The highest compressive strength was the fly ash mixture with a variation of 20%, namely with a compressive strength of 45.25 MPa, which met the planned compressive strength. Where the design compressive strength is 29.3 MPa.